2015
DOI: 10.1088/1475-7516/2015/05/007
|View full text |Cite
|
Sign up to set email alerts
|

The bispectrum in the Effective Field Theory of Large Scale Structure

Abstract: We study the bispectrum in the Effective Field Theory of Large Scale Structure, consistently accounting for the effects of short-scale dynamics. We begin by proving that, as long as the theory is perturbative, it can be formulated to arbitrary order using only operators that are local in time. We then derive all the new operators required to cancel the UV-divergences and obtain a physically meaningful prediction for the oneloop bispectrum. In addition to new, subleading stochastic noises and the viscosity term… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
298
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(313 citation statements)
references
References 69 publications
14
298
1
Order By: Relevance
“…Combining these improvements leads to a model to describe the 2-point statistics with accuracy close to 1%. Although some progress have been made [19][20][21][22][23][24][25][26][27][28][29], we have not seen a similar improvement for higher-order statistics.…”
Section: Introductioncontrasting
confidence: 69%
“…Combining these improvements leads to a model to describe the 2-point statistics with accuracy close to 1%. Although some progress have been made [19][20][21][22][23][24][25][26][27][28][29], we have not seen a similar improvement for higher-order statistics.…”
Section: Introductioncontrasting
confidence: 69%
“…It is convenient to decompose the velocity field into its gradient and curl pieces. At the order we will work in this paper only the gradient component will be relevant, thus the stresses we need to model only enter through a scalar quantity: The case of the one loop bispectrum has already been considered in the literature [18,19]. In that case the second order counterterms are needed.…”
Section: The Eft Of Lssmentioning
confidence: 99%
“…In practice however, with current simulations there are significant degeneracies among these different parameters. In practice, making an ansatz for the ratios, scaling all counterterms by the same amplitude and fitting for this overall amplitude parameter, seems good enough to explain simulation measurements [18]. In this paper we are interested in performing a two-loop calculation for the power spectrum and thus we would have to model the stresses up to third order in the fields.…”
Section: The Eft Of Lssmentioning
confidence: 99%
See 1 more Smart Citation
“…An effective field theory description of the large-scale structure has been studied to constrain the dark matter three-point statistics (see Angulo et al 2014;Baldauf et al 2014). Thereafter, Kitaura et al (2014) found that a density threshold is essential to accurately model the halo three-point statistics.…”
Section: Density Threshold and Saturationmentioning
confidence: 99%